Technological Principles of Formation of Motor Competence in The Physical Education of Students With Chronic Health Conditions - V. Koryahin; O. Blavt; T. Gurtova; E. Serbo (OVS LLC, 2019)
The study objective is to determine the technological basis for the formation of motor competence of students with chronic health conditions in the process of physical education in universities.  Materials and methods. To solve the research tasks used the methods of theoretical analysis, systematization, comparison of different views on the problem under investigation, generalization of data of scientific-methodical and special literature, general-scientific methods of theoretical level: analogy, analysis, synthesis, abstraction, induction.  Results. It has been established that the quality of motor competence of students with chronic diseases is the result of an integrated organization of the educational process of physical education. It is established that information, motivational, active and reflexive competences are allocated in the structure of motor competence. As a methodological basis for the development of educational technology for the formation of motor competence of students with chronic diseases in the process of physical education during university study, the proposed technological basis of this process. They include: concretization of the ultimate goal, definition of strategic tasks, organization of actions, which involves determining the content of the pedagogical process of formation of motor competence and control and analysis of the results of this process. It is determined that the development of motor competence of students with chronic diseases in the course of physical education should result in the acquisition of a wide range of theoretical knowledge, practical skills and self-realization in the field of physical culture, aimed at improving their health and maintaining a high level of psychophysical status.  Conclusions. Formation of motor competence as a key condition for activating the qualitative psychophysical training of the future specialist involves the development and practical implementation of pedagogical technology - a well-defined algorithm of actions to ensure the effectiveness of this process.